Unique safety features and licensing requirements of the NuScale small modular reactor - Welter, Kent; Reyes, José N.; Brigantic, Adam (Frontiers in Energy Research, 2023)
Small modular reactors offer a novel approach to the construction and operation of nuclear power plants. Their design simplicity, factory manufacturing, unique passive safety features, resilience and load following capability offer a cost-effective means for introducing carbon-free power to the modern grid. This article provides an overview of the NuScale small modular reactor (SMR) technology, its safety systems, and its licensing approach. It is the first SMR to be certified by the U.S. Nuclear Regulatory Commission.